Pelatihan Sport Massage Pada Mahasiswa Pendidikan Olahraga UMNU Kebumen - Wijaya, Febri; Sumantri, Riyan Jaya; Azizah, Alfiah Rizqi; antoso, Rahmawan; Syarif, Ahmad; Irawan, Yogi Ferdy; Burhaein, Erick; Hotimah, Anisa Isna Khusnul; Irkham, Khafid; Widodo, Puput; Parmadi, Mokhamad; Widoyono, Ibnu Prasetyo (Abdibaraya, 2024)
Public Health Care in preventive and curative efforts in cases of musculoskeletal disorders that can cause a decline in a person's health and life productivity. knowledge and awareness in caring for health in oneself is an important aspect in the resilience of health degrees. Sports massage skills training is an effort to equip sports education students for affordable health care alternatives. This training went well and smoothly, providing provisions to students of sports education in human anatomy and physiology, as well as how to properly massage with the right method in accordance with the guidelines for the sequence of manipulation and movement of sports massage. Training participants are expected to know what are the indications and counter-indications when to give massage and the effects obtained from the application of massage to sportsmen and the general public, and can open up new job opportunities for sports education students in the community. It is hoped that the manipulation of sports massage can be practiced and continue to be trained so that it becomes a soft skill for students that is beneficial to the community